Local migration studies of high-Z metals in the TEXTOR tokamak. (22nd January 2016) - Weckmann, A; Petersson, P; Rubel, M; Wienhold, P; Brezinsek, S; Coenen, J W; Kirschner, A; Kreter, A; Pospieszczyk, A
Abstract: Volatile compounds of tungsten (WF6 ) and molybdenum (MoF6 ) were used as tracers of high- Z metal migration in the TEXTOR tokamak in several gas injection experiments when puffing was done through a test limiter. The experiments with W were performed prior to major shut-downs, while the MoF6 injection was followed by the final shutdown in connection with TEXTOR decommissioning. In all cases a set of surface probes and limiter tiles was retrieved and analysed with electron and ion beam techniques. The focus was on the local deposition in the vicinity of the gas inlet and in the inlet system. Depth profiles in the deposits and metal distribution maps clearly show that only near the gas inlet significant are amounts of Mo deposited along the scrape-off layer flow and E  ×  B drift directions, which could be reproduced by ERO-code modelling. Correlation between the injection scenario and the deposition patterns is presented.